Control of decentralised solar district heating. (February 2019) - Lennermo, Gunnar; Lauenburg, Patrick; Werner, Sven
Highlights: A robust control system provides a required solar circuit supply temperature. A less robust control system can give problems with oscillations in heat output. The control functions for a robust control system must be easy to understand. High solar collector efficiency requires low supply temperatures. The feed-in flow range must be large in solar district heating connections. Abstract: The purpose of decentralised solar district heating plants is to feed solar heat directly into district heating networks. This decentralised heat supply has to consider two major output conditions: a stable required feed-in supply temperature and a feed-in heat power equal to the heat output from the solar collectors. However, many installations cannot achieve the second output condition, since severe oscillations appear in the feed-in heat power. This problem can be solved by two different control concepts with either temperature- or flow-control. Detailed measurements from two reference plants are provided for these two different control concepts. One main conclusion is that a robust control system is characterized by the ability to provide required flows and temperatures. The major difference between robust and less robust control is that the supply temperatures and/or flows do not fluctuate even if the input conditions are unfavourable.